Donor-derived cell-free DNA in chronic lung allograft dysfunction phenotypes: a pilot study - Beeckmans, H.; Pagliazzi, A.; Kerckhof, P.; Hofkens, R.; Debackere, F.; Zajacova, A.; Bos, S.; Vanaudenaerde, B. M.; de Loor, H.; Naesens, M.; Vos, R. (Frontiers in Transplantation, 2024)
Long-term survival after lung transplantation is limited due to chronic lung allograft dysfunction (CLAD), which encompasses two main phenotypes: bronchiolitis obliterans syndrome (BOS) and restrictive allograft syndrome (RAS). Donor-derived cell-free DNA (dd-cfDNA) is a biomarker for (sub)clinical allograft injury and could be a tool for monitoring of lung allograft health across the (pre)clinical spectrum of CLAD. In this proof-of-concept study, we therefore assessed post-transplant plasma dd-cfDNA levels in 20 CLAD patients (11 BOS and 9 RAS) at three consecutive time points free from concurrent infection or acute rejection, during stable condition, preclinical CLAD, and established CLAD (n = 3 × 20 samples). Elevated dd-cfDNA levels were detected in 47% of stable samples, in 66% of preclinical CLAD samples, and in 71% of CLAD samples, indicating ongoing allograft injury. However, dd-cfDNA levels exhibited high intra- and interpatient variability and did not significantly differ between BOS and RAS (p = 0.25), although the range of dd-cfDNA was higher in RAS. Dd-cfDNA detects ongoing allograft injury in patients with CLAD, which warrants further investigation to improve early detection of CLAD.